2018
DOI: 10.1177/0022022117753546
|View full text |Cite
|
Sign up to set email alerts
|

A South African Experience: Cultural Determinants of Ukuthwasa

Abstract: The current study investigated ukuthwasa, a South African culture-specific syndrome associated with the calling to become a sangoma, a type of traditional healer. Ukuthwasa has previously been compared to Western mental health constructs, such as depression and schizophrenia due to its accompanying debilitating symptoms. The current study sought to better understand the calling to become a sangoma and define the phenomenology of ukuthwasa. Unstructured interviews were conducted with participants comprised of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…While there was no significant change in frequency of CAPE psychotic experiences from baseline to follow-up, there was a significant reduction of distress related to these psychotic experiences. These results are congruent with the findings of our qualitative study ( 13 ) and a qualitative study of Bakow and Low ( 16 ), which describe that ukuthwasa seems to be successful in the sense that (apprentice) THPs no longer experience distress, while the hallucinatory experiences may remain as part of the healing (divining) profession. The current study also showed reductions in psychotic symptoms and disorders as measured with the SCAN.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…While there was no significant change in frequency of CAPE psychotic experiences from baseline to follow-up, there was a significant reduction of distress related to these psychotic experiences. These results are congruent with the findings of our qualitative study ( 13 ) and a qualitative study of Bakow and Low ( 16 ), which describe that ukuthwasa seems to be successful in the sense that (apprentice) THPs no longer experience distress, while the hallucinatory experiences may remain as part of the healing (divining) profession. The current study also showed reductions in psychotic symptoms and disorders as measured with the SCAN.…”
Section: Discussionsupporting
confidence: 90%
“…Later during the process, apprentices assist their trainer while she is seeing patients. They are taught how to convey messages from the ancestors to others, how to conduct rituals and where to find traditional medicines themselves ( 13 , 16 , 18 ). By following the process of ukuthwasa , the hallucinations and other mental disturbances are believed to change from seriously disturbing at the onset, to beneficial and positive at the outcome ( 13 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakow and Low 17 suggested that the role of culture in mental health is not well understood in spite of the fact that the cultural conception of the self has a powerful influence on the manner in which the disorder is expressed and understood. Similarly, in this study, the majority of participants’ understanding of mental disorder is informed by an indigenous cultural perspective.…”
Section: Resultsmentioning
confidence: 99%
“…The role of culture produced insightful discussion during the interview regarding issues of worshiping of the ancestors, which is described as the path to healing and viewed as vital for the maintenance of health within traditional African communities. 17 The following participants demonstrate how culture influences the manner in which mental disorder is expressed and understood:…”
Section: Resultsmentioning
confidence: 99%